2023
DOI: 10.1159/000529991
|View full text |Cite
|
Sign up to set email alerts
|

Association of Four Types of Vascular Access Including Arterial Superficialization with Mortality in Maintenance Hemodialysis Patients: A Nationwide Cohort Study in Japan

Abstract: Introduction: Vascular access usage varies widely across countries. Previous studies have evaluated the association of clinical outcomes with the three types of vascular access, namely arteriovenous fistula (AVF), arteriovenous graft (AVG), and tunneled and cuffed central venous catheter (TC-CVC). However, little is known regarding the association between arterial superficialization (AS) and the mortality of patients. Methods: A nationwide cohort study was conducted using data from the Japanese Society for Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…CVCs seem the only access for patients with exhausted vessel resources. However, Murakami et al [ 16 ] recently reported that there were four types of vascular access: AVF, AVG, arterial superficialization, and TC-CVC in Japan. They found that AVF usage may have the lowest risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…CVCs seem the only access for patients with exhausted vessel resources. However, Murakami et al [ 16 ] recently reported that there were four types of vascular access: AVF, AVG, arterial superficialization, and TC-CVC in Japan. They found that AVF usage may have the lowest risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Because the JRDR only records the month of death, withdrawal of dialysis, and kidney transplantation without specific days, we assumed that each event occurred on the 15th day of the month for our estimations. 19,20…”
Section: Methodsmentioning
confidence: 99%
“…Arterio-venous fistulas (AVF) are regarded as the "gold standard" for vascular access in chronic hemodialysis (HD) patients [1] due to their extended use and association with overall lower morbidity and mortality [2]. Moreover, AVFs have lower complication rates than other vascular access (VA) types, such as central venous catheters (CVCs) or arteriovenous grafts (AVGs) [3], and they are associated with a better quality of life [4].…”
Section: Introductionmentioning
confidence: 99%